2023
DOI: 10.1101/2023.01.16.524213
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

MRI-assessed locus coeruleus contrast and functional response are not associated in young and late middle-aged individuals

Abstract: The brainstem locus coeruleus (LC) influences a broad range of brain processes, including cognition. The so-called LC contrast is an accepted marker of the integrity of the LC that consists of a local hyperintensity on specific Magnetic Resonance Imaging (MRI) structural images. The small size of the LC has, however, rendered its functional characterization difficult in humans, including in aging. A full characterization of the structural and functional characteristics of the LC in healthy young and late middl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 74 publications
0
6
0
Order By: Relevance
“…Participants further provided a subjective evaluation of their habitual sleep quality using a validated questionnaire: the Pittsburgh Sleep Quality Index (PSQI, ( 25 As already reported in this sample (27), we found significant activations within the bilateral (though more left lateralized) rostral part of the LC for the detection of the target sound (Figure 1C; p <.05, FWE corrected for multiple comparisons over the group-wise LC-mask), supporting a robust LC activation during the oddball task. Individual estimates of LC activity were then extracted within the entire individual LC masks in the participant brain space, for higher accuracy, and contrasted against the sleep metrics of interest.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Participants further provided a subjective evaluation of their habitual sleep quality using a validated questionnaire: the Pittsburgh Sleep Quality Index (PSQI, ( 25 As already reported in this sample (27), we found significant activations within the bilateral (though more left lateralized) rostral part of the LC for the detection of the target sound (Figure 1C; p <.05, FWE corrected for multiple comparisons over the group-wise LC-mask), supporting a robust LC activation during the oddball task. Individual estimates of LC activity were then extracted within the entire individual LC masks in the participant brain space, for higher accuracy, and contrasted against the sleep metrics of interest.…”
Section: Resultsmentioning
confidence: 99%
“…(C) After the baseline night, participants underwent a fMRI session during which they completed an auditory oddball task. Brain responses to the deviant tones are displayed as in (27) over the group average brain structural image [top row; p<.001 uncorrected, right color legend refers to t-values between 3.26 – red - and 8 – yellow] (top) and only over the group-wise of the LC built based on individual LC masks (bottom ro; p<.05 FWE corrected).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, as noted above, Feige et al (2021) found reduced P2 amplitudes during phasic REM sleep in insomnia, interpreted as increased MMN, suggesting increased orienting response and concomitant arousal. MMN may be regarded as a measure of LC activation itself (Berger et al, 2023;Liao et al, 2016). First functional connectivity studies examined LC function in humans (Song et al, 2017;Zhang et al, 2016), and two studies found changed connectivity associated with anxiety or depression scores in insomnia (Gong et al, 2021;.…”
Section: Rem Sleep Regulation and Instabilitymentioning
confidence: 99%